Validity of A Notarial Deed Made Without the Presence of the Presence - Desy Agatha Sari; Rasji (Journal of Law, Politic and Humanities, 2024)
The Notary is obliged to read the deed in the presence of the audience and therefore is obliged to face the Notary. On the other hand, it will have an impact on the deed becoming invalid and the Notary's civil liability. This research is normative legal research using statutory and case approaches, with the source of research material being secondary data obtained through a literature study. The results of this research show that, philosophically, the legality of a Notary's deed made without the presence of an audience is related to truth and justice, that with the presence of an audience, it is true that the audience is present so that he can listen to the contents of the deed read by the Notary so that the deed becomes valid because its truth can be accounted for. Juridically, the presence of an audience in front of a Notary when making a deed is a provision of Article 16 paragraph (1) letter m UUJN which states that a Notary in carrying out his or her position is obliged to read the deed in the presence of the audience so that the Notary's deed becomes valid if it is based on this juridical provision. The validity of Notarial deeds made without the presence of an audience according to Supreme Court Decision Number 1615 K/Pdt/2018/2020 is that the deeds were declared invalid and null and void, and the Notary was deemed to have committed an unlawful act because the plaintiff was proven to have never appeared before the Notary.